A BRCA1 promoter variant (rs11655505) and breast cancer risk - Verderio, Paolo; Pizzamiglio, Sara; Southey, Melissa C.; Spurdle, Amanda B.; Hopper, John L.; Chen, Xiaoqing; Beesley, Jonathan; Schmutzler, Rita K.; Engel, Christoph; Burwinkel, Barbara; Bugert, Peter; Ficarazzi, Filomena; et al. (Journal of medical genetics, 2010)
BACKGROUND A study of Chinese women recently suggested that the minor allele of rs11655505 in the BRCA1 promoter (c.-2265C–\textgreaterT) increases promoter activity and has a protective effect on breast cancer risk. METHODS We genotyped rs11655505 in 2912 female breast cancer cases and 2783 unaffected female controls from four Caucasian breast cancer studies. RESULTS No evidence for an association between rs11655505 and breast cancer risk was found. CONCLUSIONS Our study failed to confirm a role of rs11655505 in breast cancer risk. Larger studies are necessary to determine if there is a weak association between this SNP and breast cancer risk.